2011
DOI: 10.2514/1.j050173
|View full text |Cite
|
Sign up to set email alerts
|

Response of a Hypersonic Boundary Layer to Wall Blowing-Suction

Abstract: In the laminar-turbulent transition of boundary-layer flows, the spatial development of boundary-layer waves, especially that of unstable waves, is important and indispensable. In this paper, the response of a Mach 8 flow over a 5.3 half-angle sharp wedge to wall blowing-suction is studied by numerical simulations. Steady base flow is obtained by solving the compressible Navier-Stokes equations with a combination of a fifth-order shock-fitting method and a second-order total-variation-diminishing scheme. In st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 25 publications
4
18
0
Order By: Relevance
“…Recently, the biorthogonal multimode decomposition was used to analyze perturbations in compressible and incompressible boundary layers (Tumin 2003). Tumin et al (2007Tumin et al ( , 2011 applied the multimode decomposition to analyze DNS results of hypersonic boundary layers over a flat plate ) and a sharp wedge (Wang et al 2011c). Figure 16 compares the theoretically predicted receptivity coefficient with that filtered out from the computational results for the case of a Mach-8 flow over a sharp wedge.…”
Section: Theoretical Analysis Of Direct Numerical Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the biorthogonal multimode decomposition was used to analyze perturbations in compressible and incompressible boundary layers (Tumin 2003). Tumin et al (2007Tumin et al ( , 2011 applied the multimode decomposition to analyze DNS results of hypersonic boundary layers over a flat plate ) and a sharp wedge (Wang et al 2011c). Figure 16 compares the theoretically predicted receptivity coefficient with that filtered out from the computational results for the case of a Mach-8 flow over a sharp wedge.…”
Section: Theoretical Analysis Of Direct Numerical Simulation Resultsmentioning
confidence: 99%
“…For small-amplitude blowing/suction, the growth rate of Mack's second mode computed by DNS agreed well with those predicted by the LST including nonparallel flow effects. Wang et al (2011c) studied the response of a Mach-8 flow over a sharp wedge to wall blowing and suction in which disturbances are introduced through an actuator on the wedge surface. Figure 7 shows the pressure perturbations along the wedge surface at the same frequency for the seven cases of simulations.…”
Section: Wall Disturbancesmentioning
confidence: 99%
“…They found that the wake vorticity field deformation at the flow around the leading edge plays a decisive role in streamwise vortex formation above the boundary layer and boundary layer distortion. Wang et al [16] investigated the response of a hypersonic boundary layer to wall blowing-suction. Stetson et al [17] investigated the hypersonic boundary layer stability of a blunt cone with 7…”
Section: Introductionmentioning
confidence: 99%
“…A straightforward way to avoid first-mode destabilization is to put porous coating only where Mack's second mode is dominant. In a previous numerical study, Wang et al 25 showed that the synchronization point of mode F and mode S plays an important role in the excitation of mode S. The results indicate that the synchronization point might be the right location to start putting porous coating.…”
Section: Increasing Of Environmental Disturbance Amplitudementioning
confidence: 95%